The Experience of Health Services in Handling Covid-19 Pandemic in Nine Provinces of Indonesia - Wahyu Pudji Nugraheni; Risky Kusuma Hartono; Hasbullah Thabrany (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Indonesia’s experience in handling the Covid-19 pandemic is essential to prepare for future pandemic.Aim: This research aims to know the experience of health services in handling Covid-19 pandemic in nine provinces of Indonesia.Methods: This research used qualitative and case study approach, with a total of 94 informants coming from all levels of health service agencies from nine provinces in Indonesia. The data collection process was carried out by in-depth interviews, and data analysis were done by means of triangulation of sources between informants.Results: Each province has a variety of local policies with the addition of varying amouns of the budget for handling Covid-19. In addition, the workload of health workers increased after the pandemic, and the availability of facilities, medicines, and single-usage medical materials were deemed inadequate in dealing with the Covid-19 pandemic.Discussions: Accounting for the use of funds for handling Covid-19 as well as increasing surveillance capacity needed to prepare for future pandemic in Indonesia.